2011
DOI: 10.1016/j.ypmed.2011.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of health outcomes among affiliated and lay disaster volunteers enrolled in the World Trade Center Health Registry

Abstract: Lay volunteers' poorer health outcomes reflect earlier, more intense exposure to and lack of protection from physical and psychological hazards. There is a need to limit volunteers' exposures during and after disasters, as well as to provide timely screening and health care post-disaster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…Thus caution must be taken in drawing inferences for the subgroup summaries based on these small numbers. Second, we only estimated crude ORs for the WTC exposure variables without adjusting for other factors, such as age, sex, socioeconomic status, and co-morbidity, which have been shown to affect PTSD outcomes [31] [32] [36] [37]. While changes in the summary ORs may be limited, as the significant associations were still present after adjusting for relevant covariates in most studies included in this meta-analysis, influences of these potential moderators and others that were not considered in the current study deserve further attention by ongoing WTC studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus caution must be taken in drawing inferences for the subgroup summaries based on these small numbers. Second, we only estimated crude ORs for the WTC exposure variables without adjusting for other factors, such as age, sex, socioeconomic status, and co-morbidity, which have been shown to affect PTSD outcomes [31] [32] [36] [37]. While changes in the summary ORs may be limited, as the significant associations were still present after adjusting for relevant covariates in most studies included in this meta-analysis, influences of these potential moderators and others that were not considered in the current study deserve further attention by ongoing WTC studies.…”
Section: Discussionmentioning
confidence: 99%
“…Psychometric properties of the PCL used in this manner in other settings and with other traumatized populations have reported sensitivity ranging from 0.94 to 0.97, specificity from 0.86 to 0.99, positive predictive value from 0.70 to 0.97, and diagnostic efficiency from 0.83 to 0.96 (Blanchard et al, 1996; Ruggiero et al, 2003; Ventureyra et al, 2002; Weathers et al, 1993). Because studies have shown that the diagnostic efficiency of the PCL is improved when using a cut-off of 44 as opposed to 50 (Blanchard et al, 1996), in this study, as well as previous Registry studies (Brackbill et al, 2009; Debchoudhury et al, 2011; Farfel et al, 2008; Li et al, 2011), enrollees with a PCL score of44 or greater at Wave 2 were considered to have probable PTSD (hereafter referred to as PTSD).…”
Section: Methodsmentioning
confidence: 98%
“…Perrin et al (2007) found that the overall prevalence of PTSD among rescue/recovery workers was 12.4%, ranging from 6.2% for trained police to 21.2% for untrained and unaffiliated volunteers 17) . Debchoudhury et al (2011) confirmed these findings and found that unaffiliated volunteers had greater risk of early mental health diagnosis, chronic PTSD, and lateonset PTSD 18) . Li et al (2011) found the incidence of postSeptember 11 GERS to be higher in individuals with asthma or PTSD than in those without either condition, and highest in those with both comorbid conditions 8) .…”
Section: The Importance Of Worker Training In Preventing Ptsdmentioning
confidence: 66%